The Prevalence of Polypharmacy in South Indian Patients: A Pharmacoepidemiological Approach - S.S, Mohammed; M.K, Sreenath; V.G, Vishnu; F, Jose; S.T, Siraj; V.P.R, Anand (Indian Journal of Pharmacy Practice)
The study conducted assessed the prevalence of polypharmacy and identified the individuals particularly at risk of polypharmacy.Data collection was based on the prescriptions collected from patient's hospital records and case sheets. The collected prescriptions were scrutinized for polypharmacy and were categorized as minor polypharmacy - concurrent use of 2 to 4 drugs; and major polypharmacy – concurrent use of five or more drugs. Out of 1003 prescriptions 630 prescriptions were found to be minor polypharmacy and 373 prescriptions were majorpolypharmacy. The results showed that major polypharmacy was more prevalent among the cardiovascular diseases (31.5%) followed by the infectious diseases (23.67%) and was seen to be least in dermatological diseases (0.67 %); the minor polypharmacy was prevalent in gastrointestinal disorders (24.07 %) followed by the infectious diseases (20.10 %) and least in dermatological diseases (1.74 %).Based on the information obtained from our study suggestions to reduce the polypharmacy related problemsare as follows: Ask patients to bring all medicines to counseling center ; Control pro re nata prescribing; Select a drug that have more than one indication; Start with low doses and titrate dose according to effect; Monitor for adverse reactions and check for potential drug interactions; Routinely check and encourage compliance; Periodically simplify the therapeutic regimen and stop drugs if possible; Educate the patient about the drug therapy and teach the patient to prioritize the currently used drugs; Place limits on the duration of drug prescribing.
Keywords: Polypharmacy; Drug therapy; Drug utilization; Prescribing pattern